High-intensity interval training prevents muscle mass loss in overweight Chilean young adults during a hypocaloric-Mediterranean diet: a randomized trial - Monsalves-Álvarez, Matías; Jiménez, Teresa; Bunout, Daniel; Barrera, Gladys; Hirsch, Sandra; Sepúlveda-Guzman, Carlos; Silva, Claudio; Rodriguez, Juan M.; Troncoso, Rodrigo; de la Maza, María Pía (Frontiers in Nutrition, 2023)
The hypocaloric Mediterranean diet (MD) mainly reduces fat mass but inevitably causes a loss of skeletal muscle mass. High-intensity interval training (HIIT) seems to have advantages in preserving muscle mass during a hypocaloric regime. Our study compares body composition and metabolic changes in overweight and obese Chilean women and men after 3 months of weight loss treatment with a Mediterranean-type hypocaloric diet, HIIT, or a combination of both. The study included 83 overweight or obese women and men between the ages of 25 and 50. The subjects were randomly assigned to one of the three intervention groups: (1) MD, (2) EX, and (3) MD + EX. Baseline and post-intervention measurements included: (a) body composition by dual-beam densitometry, muscle, and fat measurements by thigh ultrasound and computed tomography; (b) handgrip and quadriceps muscle strength; (c) exercise performance by peak oxygen consumption, peak load, work efficiency, and exercise energy expenditure; and (d) metabolic parameters. Out of 83 participants, the retention rate was 49% due to low compliance with the interventions. As expected, the MD group resulted in significantly greater weight loss (MD −7%, EX −0.6% and MD + EX −5.3%) and appendicular fat mass loss (MD −11.1%, EX −2.9, MD + EX −10.2%) but was associated with significant lean tissue loss (2.8%), which was prevented by HIIT (EX −0.1 and MD + EX −0.6%). Metabolic and glycoxidative parameters remained unchanged, irrespective of changes in body composition. Hypocaloric diets remain the most effective means to lose weight and body fat. However, it induces a loss of lean body mass when not accompanied by exercise training. This study shows that HIIT prevents the loss of muscle mass caused by a hypocaloric Mediterranean diet.